Notes on Expression GUERRILLA WAR - Połowniak-Wawrzonek, Dorota (Respectus Philologicus, 2017)
The word combination guerrilla war has a terminological meaning ‘war, during which the weaker side uses the tactics of avoiding general battles and combats unexpected enemy attacks with the help of small military units or partisans’. The combination guerrilla war is associated by users of common language primarily with semantic elements such as ‘a scope of insidious, hidden and difficult to predict, tiring opponent actions’. In the modern texts, the term guerrilla war can undergo a metaphorisation process – it is a determinologisation of multiword expression of military terms. In the figurative sense of the verbal connection guerrilla war there are characterised semantic elements as ‘set of insidious actions, hidden, difficult to predict, directed against to someone or to something, to achieve something, teasing the opposite side, her fatigue, limiting its influence’. In some texts determinologisation signals were presented – a change of component pattern, clauses appeared, which indicates metaphorisation of compound, for example: tax guerrilla war, office guerrilla war. The texts which reported metaphored military term guerrilla war featured the following metaphors: POLITICS is a WAR, ECONOMIC PERFORMANCE is a WAR, DIFFERENT, SPECIAL ACTIVITIES and FORMS OF COMPETITION is a WAR.